Yearbook of International Sports Arbitration 2016 (Yearbook of International Sports Arbitration, 2018)
The Yearbook of International Sports Arbitration is the first academic publication aiming to offer comprehensive coverage, on a yearly basis, of the most recent and salient developments regarding international sports arbitration, through a combination of general articles and case notes. The present volume covers decisions rendered by the Court of arbitration for Sport (CAS) and national courts in 2016. It is a must-have for sports lawyers and arbitrators, as well as researchers engaged in this field. It provides in-depth articles on burning issues raised by international sports arbitration, and independent commentaries by esteemed academics and seasoned practitioners on the most important decisions of the year by the CAS and national courts. Dr. Antoine Duval is Senior Researcher for International and European Sports Law at the T.M.C. Asser Instituut in The Hague. He holds a Ph.D. on the interaction between Lex Sportiva and EU Law from the European University Institute in Florence. Prof. Antonio Rigozzi teaches international arbitration and sports law at the University of Neuchâtel, Switzerland, and is the partner in charge of the sports arbitration practice at Lévy Kaufmann-Kohler, a Geneva-based law firm specializing in international arbitration.